Numerical modelling of plasma production with radio-frequency heating using four-strap π-phased antenna - Kulyk, Yu.S.; Moiseenko, V.Е.; Wauters, T.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2014)
Results of calculations of radio-frequency (RF) plasma production in the ion-cyclotron range of frequencies (ICRF) in the Uragan-2M stellarator using four-strap π-phased antenna are presented. The analysis carried out with usage of a self-consistent model that simulates plasma production with ICRF antennas. Представлены результаты расчетов по ВЧ-созданию плазмы в ионно-циклотронном (ИЦ) диапазоне частот в стеллараторе Ураган-2М с использованием четырехполувитковой π-фазированной антенны. Теоретический анализ проводился с помощью самосогласованной модели, которая моделирует создание плазмы с использованием ИЦ-антенн. Представлено результати розрахунків з ВЧ-створення плазми в іонно-циклотронному (ІЦ) діапазоні частот у стелараторі Ураган-2М з використанням чотирьохнапіввиткової π-фазованої антени. Теоретичний аналіз проводився за допомогою самоузгодженої моделі, що моделює створення плазми з використанням ІЦ-антен